Users’ Perceptions on The Role of Recreational Parks in Societal Development: A Public Administration Study of Akure, Ondo State, Nigeria. - Fadeke, Owolabi; Bassey Ikike Ibanga; Isanyinka Stephen Oluwabukunmi; Yamah Daniel Olugbenga (Jurnal Administrasi Publik (Public Administration Journal), 2023)
Our cities gain from recreational parks' fundamental environmental, aesthetic, and recreational benefits. They also bring great economic benefits to any country. The purpose of this research is to assess Citizens' views on the state of three recreational parks and landscaping in Akure, Ondo State. The study aims to evaluate three recreational parks and landscaping in Akure, Ondo State, Nigeria, their properties, their impact on users, and the contribution of recreational landscapes to societal development and revenue generation. This paper also suggests better ways to maintain these recreational parks. Gardens with a broad assortment of trees and other plants are a significant recreational feature in developing countries like Nigeria. Urban and recreational facilities have been seen as a tool to improve living conditions in Ondo State. One of the most difficult aspects of maintaining recreational parks is balancing the needs of different user groups, such as those seeking solitude and those seeking raucous play and picnicking. Parks and recreation are typically the "engine" of local tourism. In a simplified tourism model, people leave their homes and travel to attractions supported by services such as hotels/motels, restaurants, and commerce.